Induction of Agarwood (Aquilaria sp.) Shoots With Benzyl Adenine Purine in Vitro - Dewi Yana; Mulyanti Mulyanti; Oktarisa Nurul Mukminin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The rising international demand for agarwood has led to excessive harvesting from natural populations, creating serious concerns regarding the sustainability of this valuable resource. Therefore, the development of efficient and sustainable propagation methods has become increasingly important. One promising approach is in vitro culture, which enables large-scale plant multiplication. Nevertheless, the response of agarwood explants to cytokinin treatments, especially Benzyl Amino Purine (BAP), has not been clearly established. This study aimed to evaluate the effect of different concentrations of BAP on the formation of shoots and leaves in agarwood explants cultured under laboratory conditions. The experiment was conducted in 2008 at the Tissue Culture Laboratory, Syiah Kuala University, Banda Aceh. A Completely Randomized Design (CRD) with a single factor was employed. Seven BAP concentrations were tested with seven replications, resulting in a total of 49 experimental units. The treatments consisted of 0, 0.1, 0.3, 0.5, 0.7, 0.9, and 1.1 mg L⁻¹ BAP added to Murashige and Skoog (MS) culture medium. Observations on growth responses were recorded for eight weeks after culture initiation. The results of statistical analysis indicated that the variation in BAP concentration did not significantly influence the number of shoots or leaves produced by the explants. However, descriptive observations showed that the medium containing 0.3 mg L⁻¹ BAP tended to support relatively better growth compared with the other treatments. These findings imply that the tested BAP levels were not sufficiently effective in significantly stimulating the in vitro growth of agarwood explants. The study provides additional insight into the cytokinin response of agarwood under tissue culture conditions and may serve as a reference for future optimization of culture media to improve large-scale propagation strategies.